I wonder why Greeks built temples and other questions about ancient china - MacDonald, Fiona (New York : Kingfisher, 1999)
Questions and answers introduce the clothing, food, weapons, religion, and other aspectsof daily life in ancient greece
Keywords: Greece-Civilization-Juvenile literature; Greece-Civilization-Questions and answers